MiR‐125a‐5p impairs endothelial cell angiogenesis in aging mice via RTEF‐1 downregulation. Issue 5 (24th July 2014) - Che, Peng; Liu, Jun; Shan, Zhen; Wu, Ridong; Yao, Chen; Cui, Jin; Zhu, Xiaonan; Wang, Junwei; Burnett, Mary Susan; Wang, Shenming; Wang, JinSong
Summary Increasing evidence suggests that microRNAs (miRNAs) play important roles in impaired endothelial cell (EC) angiogenesis during aging. However, their exact roles in the aging process remain unclear. We aimed to determine whether miRNAs cause angiogenesis defects in ECs during aging and to uncover the underlying mechanisms. To study the miRNA‐induced changes in ECs during aging, we performed microarray analyses on arterial ECs collected from young and aging mice. Using qRT–PCR, we showed that microRNA‐125a‐5p (mir‐125a‐5p) expression was approximately 2.9 times higher in old endothelial cells (OECs) compared with samples collected from young animals. Western blot assays showed a lower expression level of an mir‐125a‐5p target known as related transcriptional enhancer factor‐1 (RTEF‐1) in OECs compared with its expression levels in young cells. Overexpression of mir‐125a‐5p in young endothelial cells (YECs) using pre‐mir‐125a‐5p caused the downregulation of RTEF‐1, endothelial nitric oxide synthase (eNOS) and vascular endothelial growth factor (VEGF) and resulted in impaired angiogenesis, as evidenced by spheroid sprouting and tube formation assays in vitro. Conversely, repression of mir‐125a‐5p in OECs using anti‐mir‐125a‐5p increased RTEF‐1, eNOS and VEGF expression and improved EC angiogenesis. Importantly, impaired angiogenesis caused by knock‐down of RTEF‐1 was not efficiently rescued by anti‐mir‐125a‐5p. Dual‐luciferase reporter gene analysis showed that RTEF‐1 is a direct target of mir‐125a‐5p, which regulates angiogenesis by repressing RTEF‐1 expression and modulating eNOS and VEGF expression. These findings indicate that mir‐125a‐5p and RTEF‐1 are potential therapeutic targets for improving EC‐mediated angiogenesis in elderly individuals.